Jan Tinbergen (1903-1994) and the rise of economic expertise - Dekker, Erwin 1984- (Historical perspectives on modern economics, 2021)
Jan Tinbergen was the first Nobel Prize winner in Economics and one of the most influential economists of the 20th century. This book argues that his crucial contribution is the theory of economic policy and the legitimation of economic expertise in service of the state. It traces his youthful socialist ideals which found political direction in the Plan-socialist movement of the 1930s for which he developed new economic models to combat the Great Depression. After World War II he was able to synthesize that work into a theory of economic policy which not only provided a lasting framework for economic policy around the world, but also secured a permanent place for economic experts close to government. The book then turns to an examination of his attempt to repeat this achievement in the development projects in the Global South and at the international level for the United Nations